2019
DOI: 10.1093/mnras/stz1746
|View full text |Cite
|
Sign up to set email alerts
|

No signs of star formation being regulated in the most luminous quasars at z ∼ 2 with ALMA

Abstract: We present ALMA Band 7 observations at 850µm of 20 luminous (log L bol > 46.9 [erg s −1 ]) unobscured quasars at z ∼ 2. We detect continuum emission for 19/20 quasars. After subtracting an AGN contribution, we measure the total far-IR luminosity for 18 quasars, assuming a modified blackbody model, and attribute the emission as indicative of the star formation rate (SFR). Our sample can be characterized with a log-normal SFR distribution having a mean of 140 M yr −1 and a dispersion of 0.5 dex. Based on an infe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 160 publications
(253 reference statements)
8
49
1
Order By: Relevance
“…These results, albeit with more evidence, are still consistent with the tentative findings of B19, which showed that more luminous X-ray AGNs have R MS distributions closer to those of main-sequence galaxies compared to lower L X AGNs. This is also consistent with the findings of Schulze et al (2019), who noticed no difference in the SFR distribution of 20 z ∼ 2 quasars and the SFR distribution of main-sequence galaxies.…”
Section: R Ms As a Function Of L Xsupporting
confidence: 93%
“…These results, albeit with more evidence, are still consistent with the tentative findings of B19, which showed that more luminous X-ray AGNs have R MS distributions closer to those of main-sequence galaxies compared to lower L X AGNs. This is also consistent with the findings of Schulze et al (2019), who noticed no difference in the SFR distribution of 20 z ∼ 2 quasars and the SFR distribution of main-sequence galaxies.…”
Section: R Ms As a Function Of L Xsupporting
confidence: 93%
“…This choice is motivated by the ALMA study of Scholtz et al (2018) which constrained the empirical IR distributions of X-ray AGN in deep extragalactic fields. Very luminous QSOs at z ∼ 2 may show a narrower distribution of SFRs (width ≈ 0.5; Schulze et al 2019), but this level of difference in the assumed distribution width makes little qualitative difference to our results. For any given interval in redshift, we identify all cQSOs in the LoTSS DR1 field, irrespective of their radio properties.…”
Section: Simulating the Sfr Contribution In Typical Qsoscontrasting
confidence: 50%
“…The first approach assumes that QSOs exhibit a lognormal distribution of IR luminosities arising from SF. This assumption is motivated by ALMA continuum studies of distant AGN and QSOs (Scholtz et al 2018;Schulze et al 2019), as well as theoretical considerations from hydrodynamic simulations (Scholtz et al 2018). The second approach modifies the redshiftdependent infrared luminosity functions (IRLFs) of galaxies to construct IR luminosity distributions tuned to QSOs.…”
Section: Simulating the Sfr Contribution In Typical Qsosmentioning
confidence: 99%
“…In a sample of 18 quasar host galaxies studied in dust continuum with ALMA, Schulze et al (2019) find no evidence for regulation of star formation. Their sample matches ours in both bolometric luminosity and SMBH mass.…”
Section: Gas Depletionmentioning
confidence: 86%